Disseminated melioidosis involving skin and joint: a case report (Ibrahim Medical College Journal, 2016)
Melioidosis is an infectious disease that can cause serious morbidity and may result in death if not treated early. Its causative organism, Burkholderia pseudomallei is present in soil and water. Here, we report a case of disseminated melioidosis involving skin and joint in a farmer residing in an area where the organism has been found in the soil.Ibrahim Med. Coll. J. 2015; 9(2): 55-57